PEMBUATAN GAME EDUKASI BERBASIS ANDROID GUNA MELATIH DAYA INGAT ANAK (STUDI KASUS: 4-6 TAHUN) - Puji Zulaikasari; Syalis Ibnih Melati Istini; Andi Irawan (Asosiasi Dosen Muda Indonesia, 2023)
Memory is a person's ability to store, process, and retrieve information that has been absorbed by the brain. Neutron elements produced by the brain play a role in storing information. When the brain is stimulated to produce neutrons intensively, memory will become sharper. Based on these problems, the authors are interested in making an educational game to train the memory of children 4-6 years based on Android. There are several software used in making this math educational game such as Adobe Photoshop CC 2018, DB Browser (SQLite), and Android Studio. The result of this scientific writing is in the form of a matchmaking game application for kids. With this application, it is proven to be able to train children's memory and make the learning process fun. Keywords: Android, Educational Game, Memory.